The fungi - Carlile, M. J. (Academic Press, 2001)
The fungi are one of the great groups of living organisms, comparable in numbers of species, diversity and ecological significance with animals, plants, protists and bacteria. This textbook deals with all fundamental and applied aspects of mycology, illustrated by reference to well studied species from major fungal groups. Since the publication of the first edition of The Fungi, there have been many important advances in the field of mycology. This second up-to-date edition has been revised and substantially expanded, and incorporates the application of methods of molecular biology, especially DNA technology to mycology.